Manajemen Pembelajaran Berdiferensiasi PAI Kurikulum Merdeka Pada SMKN 1 Bakam - Kusumardi, Adi Adi (Scientia: Jurnal Hasil Penelitian, 2024)
This research is based on failure and ignorance in managing learning for teachers, students and the learning process. Learning using conventional methods (teacher center) without distinguishing between the various characteristics of students results in monotonous learning and tends to be more passive. Therefore, religious learning and morals have not shown results that are in accordance with educational goals and the application of PAI learning in everyday life is less than optimal. This causes complex moral degradation in students both as perpetrators and victims. The aim of writing this thesis is to explain PB management and its implementation in PAI lessons at SMKN 1 Bakam. This type of research is qualitative research with descriptive methods and uses a phenomenological approach. The data collection methods used were interviews, observation and documentation. Then the data is analyzed using a data reduction pattern, data presentation followed by drawing conclusions. The data collection technique was carried out using purposive sampling followed by testing the validity of the data in the form of triangulation. This research was conducted at a vocational school center of excellence as a pilot project. PAI differentiated learning management in the independent curriculum at SMKN 1 Bakam uses 5 patterns, namely: (a) Preparation of KOSP (vision, mission and goals); (b) Preparation of learning administration and learning tools; (c) Implementation of differentiated learning; (d) Carry out academic supervision; (e) Formative assessment and summative assessment. Management of differentiated learning implementation is carried out with steps: 1). Develop learning administration (effective week, prota, prosem) and learning tools (CP, TP, ATP and teaching modules); 2). Conditioning teaching materials with methods, media and learning environments; 3). Carry out differentiated learning with steps: Pre-activity (non-cognitive and cognitive assessment); initial activities of content differentiation (material, interests and learning styles); core activities of process differentiation (use of methods, models and media), product differentiation (goods, services); Concluding activities with formative assessment activities; 4). Conduct learning assistance; 5). Conduct summative assessments